2002
DOI: 10.1063/1.1457465
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationarity of strong collisionless quasiperpendicular shocks: Theory and full particle numerical simulations

Abstract: Whistler waves are an intrinsic feature of the oblique quasiperpendicular collisionless shock waves. For supercritical shock waves, the ramp region, where an abrupt increase of the magnetic field occurs, can be treated as a nonlinear whistler wave of large amplitude. In addition, oblique shock waves can possess a linear whistler precursor. There exist two critical Mach numbers related to the whistler components of the shock wave, the first is known as a whistler critical Mach number and the second can be refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
197
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(220 citation statements)
references
References 29 publications
(35 reference statements)
18
197
1
1
Order By: Relevance
“…Also, the fraction of reflected ions was seen to vary strongly, and bursts of high-frequency waves were seen. The interpretation was that the reformation was driven by a fluctuating reflected fraction, and the generation of non-stationary whistler wave packets followed the reformation mechanism proposed by Krasnoselskikh et al (2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the fraction of reflected ions was seen to vary strongly, and bursts of high-frequency waves were seen. The interpretation was that the reformation was driven by a fluctuating reflected fraction, and the generation of non-stationary whistler wave packets followed the reformation mechanism proposed by Krasnoselskikh et al (2002).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Comişel et al (2011) performed 1-D PIC simulations and made comparisons with the same shock crossing studied by Lobzin et al (2007). Based on the simulation results, they concluded that the high-frequency fluctuations were due to the modified two-stream instability (MTSI), rather than the whistler gradient catastrophe model of Krasnoselskikh et al (2002). It could be noted that the use of a 1-D simulation introduces some strong assumptions about the microstructure of the shock, which could affect comparisons with observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the theoretical approaches to MHD turbulence in astrophysical shocks, one finds e.g. Krasnoselskikh et al (2002), who performed numerical studies of MHD shocks in one dimension, describing the quasi-perpendicular shock as a superposition of Whistler waves. Lembege et al (2004) studied multiple unresolved topics of the shock transition such as the problems already mentioned earlier in this text, including shock front nonstationarity, electron heating, and particle diffusion in turbulent media, using theoretical and numerical methods.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
“…This mechanism predicts a timescale for reformation of the order of the ion cyclotron period [Chapman et al, 2005]. Nonstationarity has also been suggested to be the outcome of a gradient catastrophe of nonlinear upstream whistler, associated with Mach numbers greater than the (nonlinear) whistler critical Mach number beyond which an upstream whistler cannot phase stand in the upstream flow 98 [Krasnoselskikh et al, 2002]. An alternative mechanism found in particle-in-cell (PIC) simulations is the quasi-periodic disruption of the ion foot due to the modified two-stream instability [Scholer and Matsukiyo, 2004].…”
Section: Introductionmentioning
confidence: 99%